Visual metaphor structure and process - Steen, Gerard (Converging evidence in language and communication research ;, 2018)
Metaphor has recently been reconceptualised as a fundamental part of the human conceptual system. It can hence be expressed in language but also in other modalities and media of communication, including gesture and body language, sound and music, and film and visuals. In spite of this theoretical landslide, however, the wide range of nonverbal metaphor and its processing has neither been empirically investigated on the same scale nor with the same rigour as metaphor in language. The overarching goal of this book is to report on the findings of a research program aimed at exploiting the vast cognitive linguistic and psycholinguistic expertise on metaphor in language for a new, behaviourally founded approach to the structure and processes of metaphor in one of these nonverbal manifestations, namely static visuals. The book presents concepts and methods for the identification and analysis of metaphor in document structure as well as new approaches to the study of visual metaphor processing. Its results are intended to further the development of an encompassing and robust cognitive-scientific theory of metaphor by including visual metaphor while also enriching our understanding of the communicative possibilities and effects of visual metaphor in multimodal discourse.